Complaining about rivals: Indifference, cooperation, and competition in the governance of advertising - Cluley, Robert (Wiley, 2018)
What should rivals do when they see competitors breaking agreed rules within systems of self-regulation? This study investigates compliant behaviour among UK advertisers to answer this question empirically. It analyses five years of complaints (N=146,062) and adjudications (N=4,832) published by the self-regulatory body for the UK advertising industry. The majority of firms adopt a strategy of indifference and rarely regulate their rivals. Highly engage firms either adopt an angelic strategy as they use their resources to complain about their rivals; a deviant strategy as they are subject to a large number of complaints; or a predatory strategy as they attack their rivals through advertising regulation. This illustrates a unique form of regulatory capture in which a regulatory system becomes an arena of competition for some actors while continuing as a governance mechanism for others.